2019
DOI: 10.3390/polym11061021
|View full text |Cite
|
Sign up to set email alerts
|

Crowding-Activity Coupling Effect on Conformational Change of a Semi-Flexible Polymer

Abstract: The behavior of a polymer in a passive crowded medium or in a very dilute active bath has been well studied, while a polymer immersed in an environment featured by both crowding and activity remains an open problem. In this paper, a systematic Langevin simulation is performed to investigate the conformational change of a semi-flexible chain in a concentrated solution packed with spherical active crowders. A very novel shrinkage-to-swelling transition is observed for a polymer with small rigidity. The underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Activity was independently shown to enhance the looping probability of chromatin segments [ 52 ]. Of note, there are hints that crowding may further promote blob formation in a crowder size- and concentration-dependent manner [ 53 ], and taking into account hydrodynamic interactions may result in even further shrinkage of polymers [ 54 ]. Interestingly, a simulation involving ensembles of active semiflexible polymers showed that the different polymers also get closer with increasing activity [ 38 ], suggesting that activity can enhance chromatin fiber density which may, in turn, promote blob formation.…”
Section: Discussionmentioning
confidence: 99%
“…Activity was independently shown to enhance the looping probability of chromatin segments [ 52 ]. Of note, there are hints that crowding may further promote blob formation in a crowder size- and concentration-dependent manner [ 53 ], and taking into account hydrodynamic interactions may result in even further shrinkage of polymers [ 54 ]. Interestingly, a simulation involving ensembles of active semiflexible polymers showed that the different polymers also get closer with increasing activity [ 38 ], suggesting that activity can enhance chromatin fiber density which may, in turn, promote blob formation.…”
Section: Discussionmentioning
confidence: 99%
“…Looping may be further stabilized by DNA bridging factors and/or SMC proteins at the loop bases 48 as well as a host of transcription factors operating as dimers. Of note, there are hints that crowding may further promote blob formation in a crowder size and concentration-dependent manner 49 , and taking into account hydrodynamic interactions can lead to even further shrinkage of polymers 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenology exhibited by active polymers is heterogeneous, ranging from translational [94,95] to reptation motion [88,89], swelling [52,53,96], looping [55], swirling [97], or shrinkage [98,99], according to the different parameters characterizing the active polymer model scrutinized.…”
Section: Introductionmentioning
confidence: 99%